3-Cylinder gasoline direct injection as opposed to 4-cylinder multi-port fuel injection for lower fuel consumption and NOX emission - Mohiuddin, A. K. M.; Mohd Sood, Anwar (IIUM Press, 2011)
The need for an engine that offers a low fuel consumption and good low-end torque grown for the past few years. The European environment protection agencies have drawn d<J the emission limits annually with emerging countries has started to adopt the European legislation. OEMs world wide have strived to meet the stringent regulation that made them develop smaller engine capacity with high low-end torque. Furthermore, continuously increas price of the fuel requires improving the engine efficiency. Electronic controlled Multi-Port Fuel Injection (MPFI) systems instead of fuel system with carburettor have been used since 1980 Development of small vehicle segments has started to look for alternatives to meet the consumption challenge. Therefore, adoption of gasoline direct injection (GOi) fuel systems new small engines hopefully can reduce hydrocarbon emissions by having fuelling and controls separated. Both 3-cylinder and 4-cylinder base engine configurations will be ex}: for the same engine capacity of 1.2 L. Improvements in hydrocarbon emissions, heat losses scavenging will be compared bet\veen the engmes. Plus, factors of packaging and considerations will also be look upon.